The predicates and their conditions in Surat Al-Qalam - Al-Alwani, Qassim Mukhlif Obaid (Al-Adab Journal, 2022)
This study deals with the grammatical methods of the pronouns in Surat Al-Qalam, and it attempts to reveal the secrets of these structures and patterns, and highlights the semantic aspects that are related to them, as well as consistency.The coherence between the structures, and their significance.The researcher divided the study into an introduction, three sections, conclusions and a conclusionAs for the introduction, it included the definition of Surat Al-Qalam, and the role of the predicates and their conditions in this blessed SurahAs for the first topic, it included:The first requirement: the definition and reasons for the revelation of Surat Al-QalamThe second requirement: The virtue of Surat Al-Qalam The second topic: The subject and the news in Surat Al-Qalam The first requirement: The subject in Surat Al-Qalam The second requirement: The news in Surat Al-Qalam.